Relationship Between Socio-Demographic Characteristics, Reproductive Health Behaviors, and Health Literacy of Women in Serbia - Maricic, Milena; Stojanovic, Goran; Pazun, Vanja; Stepović, Milos; Djordjevic, Ognjen; Macuzic, Ivana Zivanovic; Milicic, Vesna; Vucic, Veroljub; Radevic, Svetlana; Radovanovic, Snezana (Frontiers in Public Health, 2021)
Introduction: Health literacy of women can significantly affect different aspects of reproductive health. The aim of this study was the assessment of relationship of health literacy, socio-demographic characteristics and reproductive health behaviors of women in Serbia. Methodology: This was a cross-sectional study on a random sample of women aged 18 and over from the territories of three Serbian regions, stratified according to age groups, region and type of settlement. A standardized version of the European Health Literacy Survey Questionnaire (HLS-EU-Q47) was used in assessing health literacy of women. Results: Based on the calculated index of health literacy, 9.6% of respondents had inadequate health literacy. Inadequate levels of health literacy were more common in women living in rural areas (OR = 1.111) and the poorer classes (OR = 5.122). Employed women (OP = 1.249), with good health (OR = 1.512) with a degree (OR = 1.535) had bigger odds to have adequate health literacy. Multivariate regression analysis showed the following significant predictors: commitment to the chosen gynecologist (OR = 1.530), contraceptive use (OR = 1.020), knowledge of the damages that could be caused by the human papillomavirus (HPV) (OR = 1.578), awareness of vaccine availability against HPV infection (OR = 1.217) and following the health-related topics (OR = 2.350). Conclusion: Limited levels of health literacy were significantly higher among middle-aged women, among those living in rural areas, among women who rated their health as poor or very poor, and who exhibited more negative patterns of reproductive health behavior, indicating the need for implementation of prevention programs and strategies with the aim of increasing the level of health literacy.